Population Genetic Structure of Clarias teijsmanni (Family : Claridae) - Rosy, Anak Tulu. (University Malaysia Sarawak, UNIMAS., 2013)
Mitochondrial DNA of cytochrome oxidase I (COI-2) gene was used to study the population genetic Clarias teijsmanni. A total 682 bp of COI-2 gene from 12 samples were analyzed using molecular technique. Two locations were selected in this study include Kubah National Park population and Gunung Gading National Park population. The gene flow between populations was high. This study showed that the species shared same genetic. This shows that this species moving actively in the study sites. Mitochondrial DNA is useful as genetic marker for population genetic study. This study should be done in future to study the overall population genetic structure of C. teijsmanni in Sarawak.